Plant‐Derived Heterocyclic Compounds: A Promising Review on Natural Remedies for Rheumatoid Arthritis Management and Their Mechanistic Insights in Inflammation and Joint Protection - Jindong Dai; Xue Xia; Xincheng Hu; Thangamani Kanagaraj; Kanagaraj Rajalakshmi; Mangirish Deshpande; Natarajan Kiruthiga; Dongwei Zhu; Yisun Fan (Basic & Clinical Pharmacology & Toxicology, 2026)
ABSTRACT Rheumatoid arthritis (RA) represents a persistent autoimmune disease that causes continuous joint inflammation and results in synovial tissue overgrowth and worsening cartilage breakdown together with degeneration of bones. The existing pharmaceutical treatments provide symptom management although they create important adverse effects and raise ongoing security concerns. Plant‐derived heterocyclic compounds present themselves as promising pharmaceutical substitution options because they demonstrate a wide spectrum of bioactivities that include anti‐inflammatory protection together with immunomodulatory and antioxidative properties. This review investigates the therapeutic properties of natural heterocyclic compounds principally including flavonoids, alkaloids, coumarins and terpenoids for RA treatment. Medical plants contain these abundant compounds that adjust inflammatory pathways consisting of NF‐κB, MAPK and JAK/STAT to decrease pro‐inflammatory cytokines TNF‐α, IL‐1β and IL‐6 and restrict synovial fibroblast proliferation. The heterocyclic compounds found in medicinal plants also protect joints through two mechanisms: by improving antioxidant defences and activating cartilage repair. In addition to laboratory and animal test results the study evaluates how these natural compounds work together when combined in treatment plans. Research into structure–activity interactions of heterocyclic compounds alongside their molecular targets enables better development of safe plant‐derived drugs. The research review demonstrates that plant‐derived heterocyclic compounds need to become essential components in treating RA while promoting clinical studies to determine their human subject action and mechanism of operation.